2002
DOI: 10.1080/10575630290019976
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dihydroxy-7,8-Dihydro-β-Ionone 3- O -β- d -Glucopyranoside and Other Glycosidic Constituents from Apple Leaves

Abstract: 3,4-Dihydroxy-7,8-dihydro-beta-ionone 3-O-beta-D-glucopyranoside 1 has been isolated from a methanolic extract of apple (Malus domestica) leaves by XAD-2 adsorption chromatography and subsequent purification by high speed countercurrent chromatography (HSCCC) and HPLC. Under acidic conditions this glycoside gives rise to a number of volatile compounds including 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN) 2, which is known as an off-flavor compound in wine. In the course of the study, six additional glycoconju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Overall, the results are consistent with our present understanding of the formation routes of TDN from different degradation products of carotenoids [41,43,45,46,47,48]. As schematized in Figure 10, the most relevant precursors in grapes are not well characterized glycosides of 3,6–dihydroxy–β-ionone and of its reduction product, 3,6–dihydroxy–7,8–dihydro–β–ionone [41].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, the results are consistent with our present understanding of the formation routes of TDN from different degradation products of carotenoids [41,43,45,46,47,48]. As schematized in Figure 10, the most relevant precursors in grapes are not well characterized glycosides of 3,6–dihydroxy–β-ionone and of its reduction product, 3,6–dihydroxy–7,8–dihydro–β–ionone [41].…”
Section: Discussionsupporting
confidence: 85%
“…The fact that the combination of yeasts carrying out fermentation do not alter the relationships between TDN and vitispirane, as demonstrated in the plots shown in Figure 7, suggests that the reason why Pk provokes a reduction in the levels of both molecules is because it directly transforms the initial precursor into a different molecule that is no longer able to yield any of these molecules. It should be noted that Winterhalter et al suggested a TDN levels reduction by using baker’s yeast [47], but such a reduction involved a higher formation of vitispirane. The results presented here suggest that Pk follows a different and more efficient route in reducing the TDN levels.…”
Section: Discussionmentioning
confidence: 99%
“…Malva crispa Malvaceae Kaempferol glycosides [567] Malus domestica Rosaceae Kaempferol 3-O-rhamnoside [568] Manihot esculenta Euphorbiaceae Kaempferol 3-O-rutinoside [569] Maytenus aquifolium Pistacia vera Anacardiaceae Kaempferol [621] Pisum sativum Leguminosae Kaempferol 3-sophorotrioside [622] Planchonia grandis Lecythidaceae Kaempferol [623] Platanus occidentalis…”
Section: Family Compounds Referencementioning
confidence: 99%
“…Compared with the other major norisoprenoids, the formation of vitispiranes, actinidols, TPB, and their precursors is still poorly understood. TDN concentrations have been found to correlate positively with vitispirane, although it is possible that TDN can be reduced to the latter compound by yeast during fermentation 120 . As with TDN, a number of norisoprenoid precursors are possible for TPB.…”
Section: Norisoprenoidsmentioning
confidence: 99%